Viability of bibliographic resources for innovation of the current library in a specialized language (BEL) for the Escuela Colombiana de Carreras Industriales (ECCI). (2014)
The research project was performed looking for the importance of having a specialized languages library for the Faculty of Humanities at the Escuela Colombiana de Carreras Industriales (ECCI), it searched to explore different point of view of the students, similarities and necessities about BEL (Library specialized in languages); in order to generate changes in the current library and thus benefit students of different programs and faculty of the university. A library for students, which has bibliographic and technological resources for teaching and learning of academic training